Effect of Spin Dimensionality in the Fidelity of Spin Chain Quantum Communication - Dumigpe, Art Graeson B.; Galapon, Eric A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 29 No 1 (2017), 2017)
We consider an unmodulated linear spin chain composed of two qubits at the ends, which undergo nearest-neighbor interactions, with an arbitrary spin between them. The state of the qubit on one end is to be transmitted through the arbitrary spin and is received by the qubit on the other end with some fidelity. We look at the behavior of the average f idelity of state transfer through time as affected by the spin quantum number of the arbitrary spin in between the qubits. We f ind that the higher the spin quantum number becomes, the earlier it takes to achieve perfect or nearly perfect state transfer. Moreover, when the channel with arbitrary spin is subjected to environment interaction, results from the calculation of average fidelity suggest that increasing the spin quantum number of the channel provides a countermeasure to the effects of decoherence induced by the environment. Keywords: Quantum communications, spin chain, f idelity, open quantum system